2013
DOI: 10.7287/peerj.preprints.56
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of RNA in exosomes secreted by human breast cancer cell lines using next-generation sequencing

Abstract: Exosomes are nanosized (30-100 nm) membrane vesicles secreted by most cell types. Exosomes have been found to contain various RNA species including miRNA, mRNA and long non-protein coding RNAs. A number of cancer cells produce elevated levels of exosomes. Because exosomes have been isolated from most body fluids they may provide a source for non-invasive cancer diagnostics. Transcriptome profiling that uses deep-sequencing technologies (RNA-Seq) offers enormous amount of data that can be used for biomarkers di… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Meanwhile, these observations were confirmed by similar research on lung cancer, in which the mean overall exosome concentration and exosome miRNA concentration was significantly different from controls, while the expression profile future science group Extracellular vesicle microRNAs Review of the previously identified 12 miRNAs in exosomes was comparable to tumor tissue-derived miRNAs [45]. By using RNA-seq, it was revealed that exosome miRNA content reflected miRNA content of the donor cells [46]. In addition, Let-7 miRNA family was shown to be enriched in both cellular and extracellular fractions (exosomes and culture media) of a metastatic gastric cancer cell line, AZ-P7a, but decreased in a low metastatic cell line, AZ-521.…”
supporting
confidence: 78%
“…Meanwhile, these observations were confirmed by similar research on lung cancer, in which the mean overall exosome concentration and exosome miRNA concentration was significantly different from controls, while the expression profile future science group Extracellular vesicle microRNAs Review of the previously identified 12 miRNAs in exosomes was comparable to tumor tissue-derived miRNAs [45]. By using RNA-seq, it was revealed that exosome miRNA content reflected miRNA content of the donor cells [46]. In addition, Let-7 miRNA family was shown to be enriched in both cellular and extracellular fractions (exosomes and culture media) of a metastatic gastric cancer cell line, AZ-P7a, but decreased in a low metastatic cell line, AZ-521.…”
supporting
confidence: 78%
“…Because tumor-derived exosomes contain fragmented ribosomal RNA (24) and genomic DNA (25-27), we anticipated fragmentation of the reporter mRNA in exosomes. We therefore examined the integrity of Luc-RFP mRNA in MVs via RT-PCR using four sets of primers along the Luc coding region, shown in Fig.…”
Section: Mv-mediated Delivery Of Nucleic Acids For De Novo Expression Ofmentioning
confidence: 99%
“…These nanoscaled extracellular vesicles are actively released by cells to transfer proteins, mRNA, and noncoding RNAs between cells. Interestingly, tumor cells release exosomes at a greater rate than normal cells, which suggests that they may play an important role in cancer [15]. Some of the earliest exosome studies suggest that exosomes mediate B-cell transformations [16,17].…”
Section: Introductionmentioning
confidence: 99%